Penerapan Standarisasi Instalasi Listrik Skala Rumah Tangga bagi Kelompok PKBM Ingin Maju Kabupaten Bantaeng Sulawesi Selatan - Sari, Dessy Ana; Haripuddin; Zulhajji; Al Imran; Hilda Ashari (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2024)
Community service activities were implemented to enhance the understanding and application of electrical installation standards in Bantaeng Regency, Indonesia, by supporting the achievement of SDG 7: Affordable and Clean Energy. In this regard, a series of activities, such as presentations, field audits, and practical training, were conducted for the residents of Bantaeng Regency on the importance of compliance with PUIL. The findings showed that there is a big difference between the existing practice of electrical installation and the recommended standard. This project seeks to address this issue in pursuit of better energy efficiency, safety, and reliability for local households. These activities also profiled several challenges to the promotion of electrical safety, such as inequalities in public awareness and resource limitation. Despite these challenges, such activities show how community-based initiatives could be applied to broader goals of sustainable energy access. Future activities might consider the long-term impact of such interventions and identify ways in which these efforts may be scaled up.